Plant Defense Responses to Biotic Stress and Its Interplay With Fluctuating Dark/Light Conditions - Iqbal, Zahra; Iqbal, Mohammed Shariq; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Ansari, Mohammad Israil (Frontiers in Plant Science, 2021)
Plants are subject to a plethora of environmental cues which causes extreme losses to crop productivity. Due to sub optimal or overdose of environmental conditions, plants encounter difficulties in attaining full genetic potential for growth and reproduction. One such environmental condition is recurrent attack on plants by herbivores and microbial pathogens. To surmount such attacks, plants have developed complex array of defense mechanism. The defense mechanism can be either preformed; where toxic secondary metabolites are stored or can be inducible; where defense is activated upon detection of an attack. Plants sense the biotic stress condition, activate the regulatory or transcriptional machinery and eventually leads to an appropriate response. Plant defense against pathogen attack is well understood but interplay of different signals to generate the defense response against biotic stress still remains elusive. The impact of light and dark signals on biotic stress response needs comprehension. Light and dark alterations not only regulate defense mechanisms impacting plant development and biochemistry, but also bestows resistance against invading pathogens. The interaction between plant defense and dark/light environment activates a signaling cascade which is multi-dimensional, encompassing both biological and temporal scales. This signaling cascade acts as a connecting link between perception of biotic stress, dark/light environment and generation of appropriate physiological and biochemical response. This review highlights molecular responses arising from dark/light fluctuations vis-a-vis elicitation of defense mechanisms in plants.